The Influence of Gamification, Coin Rewards, and Monthly Events on Shopee Customer Loyalty: An Islamic Business Ethics Perspective - Risni Rigina Melati; Indra Setiawan; Sugiyanto; Makhda Intan Sanusi (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2026)
The rapid development of e-Commerce has encouraged companies to implement various digital marketing strategies to increase customer loyalty, including gamification elements, coin rewards, and monthly events. These strategies not only serve to increase user engagement but also have the potential to shape consumption behavior, which needs to be reviewed from an Islamic business ethics perspective. Furthermore, the inconsistency of previous research findings regarding the influence of these three variables on customer loyalty is an important basis for conducting this research. This study aims to analyze the influence of gamification elements, coin rewards, and monthly events on Shopee customer loyalty among students of STAI Mulia Astuti Wonogiri, both partially and simultaneously, from an Islamic business eth-ics perspective. This study employed a quantitative approach with explanatory research. The study population was STAI Mulia Astuti Wonogiri students, with a sample of 85 respondents determined using the Cochran formula and purposive sampling technique. Data were collected through a Likert-scale ques-tionnaire and analyzed using multiple linear regression with the aid of SPSS. The results showed that par-tially, gamification and coin rewards had a positive and significant effect on customer loyalty, while monthly events had no significant effect. However, simultaneously, all three variables significantly influenced customer loyalty, contributing 57.6%. From an Islamic business ethics perspective, this strategy is permissible as long as it is implemented honestly, transparently, and does not contain elements of gharar, maysir, or practices that harm consumers.